Depression and fatigue in the quality of life of women with breast cancer - Panobianco, Marislei Sanches; Magalhães, Paola Alexandria Pinto de; Oliveira, Iácara Santos Barbosa; Gozzo, Thais de Oliveira (Rev Rene, 2011)
This descriptive study, with a quantitative approach, aimed to analyze changes in the quality of life of women with breast cancer, who attended a rehabilitation service and presented signs/symptoms of fatigue and depression. The participants were 20 women who answered the questionnaire on quality of life, (QLQ-BR23). It was carried out between December 2008 and January 2009. Results showed impairment in the quality of life of these women, so that the lowest scores assessed by the questionnaire were related to sexual performance and satisfaction as well as to future perspectives and best scores related to Symptom Scale. We so concluded that there is still need for greater attention to these factors in the rehabilitation of these women.